Reintegrating Iran with the west challenges and opportunities - Elahee, Mohammad; Sadrieh, Farid; Wilman, Mike (International business and management series, 2015)
Iran is located at the cross-roads of world civilization and inter-continental trade, and has, throughout its long history, played an important role in the movement of goods, people and ideas. The political factors that have hobbled Iran's development have hitherto prevented scholars, business practitioners and policymakers fully appreciating Iran's potential as a key player in the economic, political and technological development of its region and beyond. This book provides its readers with a fuller understanding of the economic complexities of the present and the promise of a future rebirth in an important country, perhaps the last emerging market; a country whose potential has been dormant or held in check, but whose significance has remained unaffected. Although Iran is a large, untapped market and a great potential contributor to the world economy, after more than three decades of relative isolation, our knowledge of this country has been constrained by the dearth of exchanges and the opacity of Iranian society. The contributing scholars offer a broad overview of the challenges and opportunities presented by the gradual reintegration of Iran into the world economy.